Chick survival and hunting are important drivers for the dynamics of two Alpine black grouse Lyrurus tetrix populations. Issue 4 (15th October 2021) - Rotelli, Luca; Bionda, Radames; Zbinden, Niklaus; Schaub, Michael
Abstract : Alpine black grouse populations are generally declining, but the underlying demographic drivers are largely unknown. We studied the dynamics of two adjacent black grouse populations over a 20 years period in the Italian Alps that differ in hunting pressure to identify the main demographic process affecting these populations and to study the impact of hunting on males. We collected radio‐tracking data and conducted population surveys in spring to count displaying cocks and in late summer to determine the breeding success by means of pointing dogs. These different data sets were jointly analysed using a seasonal integrated population model to estimate population sizes and various demographic rates. The two populations fluctuated in size and the number of males from one population increased after hunting intensity was reduced. The main demographic rates did not differ between the populations. Adult survival was relatively low and productivity was high, so the life history shows the feature of a fast turnover species. In both populations, the variability of survival from hatching to the age of five weeks (chick survival) contributed more to the variation of the population growth rates than the variability of survival in later life‐history stages, and the former was positively affected by ambient temperatures in July, favouring chick survival. The adult sex ratio of the population where males hunting occurred was shifted towards females, but it evened over time with the reduction of hunting pressure. The adult sex ratio in the population without hunting and the chick sex ratios in both populations were even, suggesting that hunting acted as a mostly additive source of mortality.